A newly discovered etiology for infectious pulmonary nodules: “The rickettsial infection” - Fousad Chemban,; Fathima Ferzine Akkara, (Indian Journal of Case Reports, 2021)
Rickettsial infection as the cause for multiple pulmonary nodules is not previously been reported. We report two cases of rickettsial infection with multiple bilateral pulmonary nodules which is the first of its kind in the world literature. Both cases improved with doxycycline and follow-up lung imaging showed the disappearance of all pulmonary nodules after 6 weeks.